Internal Waves on the Continental Shelf of the Northwestern Arabian Gulf - Al Senafi, Fahad; Anis, Ayal (Frontiers in Marine Science, 2020)
The fluxes and turbulent mixing supported by internal waves (IWs) play a major role in transporting nutrients, affecting biological productivity and water-borne constituents such as contaminants and sediments. To better understand IWs on the continental shelf of the northwestern Arabian Gulf, off the coast of Kuwait, we conducted a study to examine the characteristics of these waves, and the associated energy cascade from IWs to turbulence. The study was conducted during midsummer (15 to 27 July, 2017), collected spatial transects and time series measurements at five moorings. Continuous turbulence profiles were taken at four locations in the vicinity of the moorings. Measurements of temperature, salinity, currents, turbidity, chlorophyll a and turbulence reveal that IW activity was consistent with the diurnal and semidiurnal tidal cycles. Based on cross-shore tracking of the IWs, we estimated that these waves propagated towards the coast at an average speed of 0.31 m/s, with amplitudes ranging from 7 to 9 m and generating intense mixing (> 10^-7 W/kg). In addition, we examined nighttime convective conditions driven by surface buoyancy flux which were estimated to contribute up to 70% of the turbulence kinetic energy (TKE) production. The results presented here shed new light on IW characteristics in the Northern Arabian Gulf, and offer the first detailed study of these waves in this region.